Importance of free access to research articles on decision to submit to the BMJ: survey of authors - Schroter, Sara (BMJ Publishing Group Ltd., 2006)
Objectives To determine whether free access to research articles on bmj.com is an important factor in authors' decisions on whether to submit to the BMJ, whether the introduction of access controls to part of the BMJ's content has influenced authors' perceptions of the journal, and whether the introduction of further access controls would influence authors' perceptions. Design Cross sectional electronic survey. Participants Authors of research articles published in the BMJ. Results 211/415 (51%) eligible authors responded. Three quarters (159/211) said the fact that all readers would have free access to their paper on bmj.com was very important or important to their decision to submit to the BMJ. Over half (111/211) said closure of free access to research articles would make them slightly less likely to submit research articles to the BMJ in the future, 14% (29/211) said they would be much less likely to submit, and 34% (71/211) said it would not influence their decision. Authors were equally divided in their opinion as to whether the closure of access to parts of the journal since January 2005 had affected their view of the BMJ; 40% (84/211) said it had, 38% (80/211) said it had not. In contrast, 67% (141/211) said their view of the BMJ would change if it closed access to research articles. Authors' comments largely focused on disappointment with such a regressive step in the era of open access publishing, loss of a distinctive feature of the BMJ, a perceived reduction in the journal's usefulness as a resource and global influence, restricted readership, less attractive to publish in, and the negative impact on the journal's image. Conclusions Authors value free access to research articles and consider this an important factor in deciding whether to submit to the BMJ. Closing access to research articles would have a negative effect on authors' perceptions of the journal and their likeliness to submit.